Human mesenchymal stromal cells do not cause radioprotection of head-and-neck squamous cell carcinoma - Rühle, Alexander; Lies, Marie; Strack, Maren; Lopez Perez, Ramon; Bieber, Birgit; Thomsen, Andreas; Bronsert, Peter; Huber, Peter E.; Heß, Jochen; Knopf, Andreas; Wuchter, Patrick; Grosu, Anca-Ligia; et al. (International journal of molecular sciences, 2022)
Radiotherapy of head-and-neck squamous cell carcinoma (HNSCC) can cause considerable normal tissue injuries, and mesenchymal stromal cells (MSCs) have been shown to aid regeneration of irradiation-damaged normal tissues. However, utilization of MSC-based treatments for HNSCC patients undergoing radiotherapy is hampered by concerns regarding potential radioprotective effects. We therefore investigated the influence of MSCs on the radiosensitivity of HNSCCs. Several human papillomavirus (HPV)-negative and HPV-positive HNSCCs were co-cultured with human bone marrow-derived MSCs using two-dimensional and three-dimensional assays. Clonogenic survival, proliferation, and viability of HNSCCs after radiotherapy were assessed depending on MSC co-culture. Flow cytometry analyses were conducted to examine the influence of MSCs on irradiation-induced cell cycle distribution and apoptosis induction in HNSCCs. Immunofluorescence stainings of γH2AX were conducted to determine the levels of residual irradiation-induced DNA double-strand breaks. Levels of connective tissue growth factor (CTGF), a multifunctional pro-tumorigenic cytokine, were analyzed using enzyme-linked immunosorbent assays. Neither direct MSC co-culture nor MSC-conditioned medium exerted radioprotective effects on HNSCCs as determined by clonogenic survival, proliferation, and viability assays. Consistently, three-dimensional microwell arrays revealed no radioprotective effects of MSCs. Irradiation resulted in a G2/M arrest of HNSCCs at 96 h independently of MSC co-culture. HNSCCs’ apoptosis rates were increased by irradiation irrespective of MSCs. Numbers of residual γH2AX foci after irradiation with 2 or 8 Gy were comparable between mono- and co-cultures. MSC mono-cultures and HNSCC-MSC co-cultures exhibited comparable CTGF levels. We did not detect radioprotective effects of human MSCs on HNSCCs. Our results suggest that the usage of MSC-based therapies for radiotherapy-related toxicities in HNSCC patients may be safe in the context of absent radioprotection.
Gesehen am 19.08.2022